HAK PEREMPUAN DISABILITAS DALAM UU. NO. 1 TAHUN 1974 TENTANG PERKAWINAN: PERSPEKTIF CONVENTION ON THE RIGHTS OF PERSONS WITH DISABILITIES (CRPD) - Habib Shulton A; Fatul Mu’in; M. Anwar Nawawi (Institut agama islam negeri Padangsidimpuan, 2020)
This paper examines injustice, discrimination and violations of the human rights of women with disabilities. Implementation and application of Article 4 paragraph 2 (point b and point c) of the Law. No. 1 of 1974 concerning Marriage is one of the factors. In addition, this discrimination is caused by several factors, including the fact that law enforcement in Indonesia is still dominated by a positivistic-legalistic paradigm and way of thinking. The law enforcement process is carried out in such a way from the perspective of legal regulations alone. As a result, written legal provisions (laws and regulations) have become the main benchmark in law. As a result, the law enforcement process becomes arid, dry from morality. The purpose of this article is to find out the rights of women with disabilities in law. No. 1 of 1974 concerning Marriage with the perspective of the Convention on The Rights of Persons with Disabilities (CRPD).